Challenging Assumptions Around Dementia User-led Research and Untold Stories - Ashworth, Rosalie (Springer Nature, 2023)
This open access book explores the expectations surrounding dementia, what it 'looks like' and how people have been treated by others. It aims to raise awareness of the different types of dementia, and how they impact the brain, body, and lived experience, including experience of Alzheimer's disease, Vascular Dementia, Posterior Cortical Atrophy, Frontotemporal Dementia, Semantic Dementia, and Lewy Body Dementia. The co-authors reflect on their experience with informal and formal care, before finishing with a focus on the spectrum of dementia research from clinical trials to user-led research. Throughout the book, co-authors have shared personal stories of how dementia has affected them and people with lived experience of dementia share what they wish people knew about living with the disease. Co-produced by people with lived experience of dementia, academics and health care professionals, this book is an accessible resource about dementia from the perspective of people actively involved in the field and essential reading for healthcare professionals wishing to learn more about the experience of this neuroprogressive condition, as well as policymakers, and members of the public.